Jacques-Louis Marin de France. Stipple engraving by A. Tardi - Auteur inconnu (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Jacques-Louis Marin de France. Stipple engraving by A. Tardi. Jacques-Louis Marin de France. Stipple engraving by A. Tardieu, 1827, after himself. Iconographic Collections Keywords: portrait prints | Jacques-Louis Marin de France | Ambroise Tardieu | stipple prints
Licence Creative Commons Attribution 4.0 via Wikimedia Commons
Keywords: iconographie; illustration; gravure; Patrimoine; Wikimedia Commons